Towards a Smarter Battery Management System - Zhi Cao; Naser Vosoughi Kurdkandi; Chris Mi (Batteries, 2025)
Batteries play a critical role in achieving a sustainable energy future, enabling the integration of renewable energy sources and supporting electrified transportation and smart grids [...]